Challenge-based Learning and Collaborative Skills - Palenti, Citra Dwi; Zulkarnain, Rufran (Universitas Negeri Semarang, 2019)
Uncoordinated collaborations make the stability of management of tourist destinations not good. Therefore, the process of tourism development has not been stable. Meanwhile, collaboration is widely regarded as one of the skills for academic and career success in the 21st century, especially on a large and challenging scale in the work team process. This collaboration tends to be able to adapt to the conditions and changes that occur. But although not limited, collaboration is a means to improve work relationships. The goal of the research on how to set up challenge-based learning to improve travel management collaboration Skills. Researchers use Challenge Based Learning (CBL) in the form of outbound games to improve the management of tourism destinations with social action research methods. The results showed that the collaboration used in the game could increase confidence, and communicate. Challenge-based learning and collaboration skills make the collaboration process between managers happen through communication in learning. The perceived change is like the use of language, the citizens learn already has the competence of Indonesian language and able to adjust to the circumstances and environment.